2010
DOI: 10.2478/v10053-008-0077-1
|View full text |Cite
|
Sign up to set email alerts
|

Configurational asymmetry in vernier offset detection

Abstract: Two psychophysical experiments were conducted at the horizontal and vertical orientations respectively, demonstrating substantial main effect of configuration, but no effect of offset direction on vernier acuity. In Experiment 1, a pair of horizontal bars were arranged side by side with a large gap between them. The observers were, on average, significantly better at discriminating a vertical offset if the right-hand bar was below the left-hand bar than vice versa, regardless of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…If the findings of Karim and Kojima (2010a) are compared to the findings about aesthetics of visual arts (see prior section) we see that there is a consistency between perceptual precision and aesthetic preference: what is oriented from left-to-right direction is more understandable and aesthetically more appealing than what is oriented from right-to-left direction, possibly due to the increased efficiency of information processing at that orientation. Though the stimuli that Karim and Kojima used in their studies were different from the stimuli used in the aesthetic judgment studies, they all possess a common feature of the directionality in their configurations (Figures 1, 2, 3).…”
Section: Directionality Bias In Line Alignment (Symmetry) Judgmentmentioning
confidence: 70%
See 4 more Smart Citations
“…If the findings of Karim and Kojima (2010a) are compared to the findings about aesthetics of visual arts (see prior section) we see that there is a consistency between perceptual precision and aesthetic preference: what is oriented from left-to-right direction is more understandable and aesthetically more appealing than what is oriented from right-to-left direction, possibly due to the increased efficiency of information processing at that orientation. Though the stimuli that Karim and Kojima used in their studies were different from the stimuli used in the aesthetic judgment studies, they all possess a common feature of the directionality in their configurations (Figures 1, 2, 3).…”
Section: Directionality Bias In Line Alignment (Symmetry) Judgmentmentioning
confidence: 70%
“…There is clear evidence of the cardinal superiority over the oblique orientation, and its neural basis (Furmanski & Engel, 2000; Li et al, 2003). In addition to the evidence of the orientation effect, some recent studies have demonstrated that our visuo-spatial performance can vary even within an orientation depending on spatial organization or layout of the stimuli (Figure 3; Karim & Kojima, 2010a,b; for a review, see Karim & Kojima, 2010c). In one study, Karim and Kojima (2010a) found that observers were generally better at discriminating a vertical offset for a pair of horizontal light bars (vernier features) arranged side-by-side with a large gap between them if the right-hand bar was below the left-hand bar than vice versa (Figure 3A,B; horizontal).…”
Section: Directionality Bias In Line Alignment (Symmetry) Judgmentmentioning
confidence: 88%
See 3 more Smart Citations